Where was Golgotha? The Philological, Biblical, Patristic, and Archaeological Evidence - Fiensy, David A. (Journal for the study of the historical Jesus, 2026)
Although the ancient church celebrated the place of Jesus’ execution inside or near the basilica later built by Constantine, in the last two hundred years, some scholars have insisted on other locations. This article surveys and analyzes six suggested sites for Jesus’ crucifixion (including three proposed in the nineteenth century, which remain surprisingly popular) but also argues for yet another (a seventh) topos as most likely. The investigation will lead us through a range of - mainly archaeological - evidence. My thesis is that the traditional site is near - but not identical to - the location of Jesus’ death.